Implementing Differentiated Instruction In Bahasa Indonesia Within The Framework Of The Merdeka Curriculum - Zulaiha, Siti (Universitas Islam Negeri Raden Intan Lampung, 2025)
This paradigm shift in learning at integrated Islamic primary school Cahaya Rabbani Kepahiang aligns with the demands of the Merdeka Curriculum, which requires teachers to implement differentiated instruction as an approach to accommodate the diverse characteristics of students in the classroom. This study aims to describe the implementation of differentiated instruction in the second-grade Bahasa Indonesia subject at integrated Islamic primary school Cahaya Rabbani Kepahiang, as well as to identify the supporting and constraining factors affecting its implementation. This research used a descriptive qualitative techniques included interviews, observations, and documentation, while data analysis involved data reduction, data display, and conclusion drawing/verification, with data validity ensured through technique triangulation. The findings indicate that (1) differentiated instruction was implemented through the stages of pre-instruction, instruction process, and reflection, with the development of two main components: process differentiation and product differentiation; (2) supporting factors included the availability of adequate facilities and enthusiastic students, whereas constraining factors comprised teachers’ limited understanding of differentiation strategies within the Merdeka Curriculum, time constraints, and fluctuating student learning motivation. In conclusion, differentiated instruction has the potential to enhance student engagement and learning outcomes when implemented effectively. Therefore, it is recommended that teachers receive ongoing professional development and sufficient time allocation to plan and execute differentiated strategies aligned with the Merdeka Curriculum